2019
DOI: 10.1111/sms.13432
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic knee control and movement strategies in athletes and non‐athletes in side hops: Implications for knee injury

Abstract: Athletes exposed to rapid maneuvers need a high level of dynamic knee stability and robustness, while also controlling whole body movement, to decrease the risk of non‐contact knee injury. The effects of high‐level athletic training on such measures of movement control have not, however, been thoroughly evaluated. This study investigated whether elite athletes (who regularly perform knee‐specific neuromuscular training) show greater dynamic knee robustness and/or different movement strategies than non‐athletic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 41 publications
1
18
1
2
Order By: Relevance
“…The study found that the groups differed significantly in PT of extensor muscles but not in PT of flexor muscles. 37 Adequate strength and ratio of the lower limbs, particularly the knee muscles, is necessary in many gymnastics tasks (e.g., landing, cutting, jumping, accelerating). PT and rate of torque development (RTD) are important variables of isometric strength in determining the athlete´s risk of injury.…”
Section: Discussionmentioning
confidence: 99%
“…The study found that the groups differed significantly in PT of extensor muscles but not in PT of flexor muscles. 37 Adequate strength and ratio of the lower limbs, particularly the knee muscles, is necessary in many gymnastics tasks (e.g., landing, cutting, jumping, accelerating). PT and rate of torque development (RTD) are important variables of isometric strength in determining the athlete´s risk of injury.…”
Section: Discussionmentioning
confidence: 99%
“…The Max curve is frequently used when it comes to evaluation of performance (Ryan et al, 2006), and since it actually represents a true hop trial, it is easily interpretable. The Mean curve is not as easy to interpret, but in the presence of higher variability between trials it should in theory be more reliable (Markström et al, 2019). Group comparisons are however based on group averages, and hence both these outcome measures provide relevant information.…”
Section: Choice Of Outcome Measuresmentioning
confidence: 99%
“…Similarly, including parts of the domain where we do not suspect any differences will also decrease the possibility of detecting significant parts. Here, we analyzed the whole jump from the take-off phase to the landing phase, but if the research question only relates to the take-off or the landing, these should be analyzed separately (as in e.g., Markström et al, 2019).…”
Section: Choice Of Multiple Joint Comparisonsmentioning
confidence: 99%
See 2 more Smart Citations